The Influence of Digital Competency and Self Leadership on Teacher Performance in Yayasan Indonesia Juara - Pajrudin, Putra Muhammad; Wahyuningtyas, Ratri (Jurnal Bisnis dan Pemasaran Digital, 2024)
Purpose: This study aims to examine teacher competence in facing 21st century education through digital competency, aneadership towards oneself through self-leadership, and its influence on teacher performance. Research Methodology: The method used in this study is quantitative. This study was descriptive and causal research. Based on their involvement, the researchers did not intervene in the data. This means that the data collected and processed were sourced directly from the respondents. Based on this unit, what is analyzed in this study is the individual. Based on the time of the study, this study belongs to the cross-section type; elements were measured only once during the research process in accordance with the applicable time and finished when this study was completed. Results: Digital competency and self-leadership have been proven to influence teacher performance. However, there was a difference in the influence of digital competency and self-leadership. The results showed that the magnitude of the influence of teachers’ digital competency on teacher performance was not very high. Self-leadership has a significant influence on teachers’ performance. This indicates that self-leadership has a greater influence on the quality or performance of a teacher in fulfilling his/her role. Conclusions: This study found that teacher performance at Yayasan Indonesia Juara School is in the good category, supported by strong digital competency (80%) and self-leadership (82%). Both digital competence and self-leadership have a significant positive impact on teacher performance. Teachers who effectively utilize digital tools and demonstrate self-leadership tend to perform better in planning, implementing, and evaluating learning. Limitations: This study was limited to teachers at Yayasan Indonesia Juara School, which may affect the generalizability of the findings to other educational institutions. Additionally, the study relied on self-reported data, which may be subject to bias. Contributions: The findings of this thesis are useful for educational institutions to determine the factors that influence teacher performance and to design effective professional development programs to improve teachers' skills and abilities. In addition, this research can be used by educators as a resource to study the impact of digital leadership and self-leadership on teacher performance.